Boundedness of the Multilinear Maximal Operator with the Hausdorff Content (Analysis in Theory and Applications, 2023)
In this paper, we establish the strong and weak boundedness of the multilinear maximal operator in the setting of the Choquet integral with respect to the $α$-dimensional Hausdorff content. Our results cover Orobitg and Verdera's results in [8].